7 Aligning Undergraduate Animal Science Curriculum with Current Disciplinary Vision. (7th December 2018) - Early, N; Fowler, D; Dunlap, K; Wickersham, T
Abstract: To address tightened operating budgets, increasing enrollment and employer expectations of today's graduates, the Texas A&M Animal Science Department embarked on a research-based curriculum redesign for the undergraduate program serving approximately 1, 200 students. This session discusses outcomes of the curriculum that resulted from concentrated efforts of a curriculum study group comprised of diverse faculty, advisors and students along with a consultant from the University Center supporting teaching and learning on campus. Existing program strengths and weaknesses were identified, stakeholder survey responses (n=289) regarding student learning outcomes gathered, and approaches to animal science curriculum existing across literature and peer institutions obtained. Stakeholders reported the measured proficiency of animal science knowledge and universal skill areas of graduates to be less than the reported importance of those same knowledge and skill areas, with a discrepancy (importance minus proficiency; on a 0–3 scale) of -0.22 and -0.56, respectively. Data supported the development of 3 disciplinary specific and 7 universal skill-based learning outcomes. Performance criteria for each of the program learning outcomes were scripted and placed in a user-friendly rubric format, and then matched with program courses and experiences such as internships. Five new courses were added to the core animal science curriculum. Members of the curriculum group met with departmental faculty members to assist with the understanding and incorporation of learning outcomes, assessments, and teaching methods into the faculty member's course plans using a customized course guide and standardized syllabus. Course documents were approved by the university in fall 2017. An implementation and assessment team now oversees the long-term success and adaptability of the curriculum. Though implementation of the process will be shared in the context of a large research-extensive U.S. university, its adaptation to a variety of programs substantiates its scope.